Literature Review: Hiit Training on Physical Fitness, Vo2max and Social Status in Adults with Sedentary Lifestyle - Yuastrian Teja Kusuma; Setyo Harmono; Atrup (Journal Coaching Education Sports, 2023)
In 2020, the World Health Organization (WHO) recommended engaging in 150-300 minutes of moderate-intensity physical activity per week, at 40-60% of the Maximal Pulse Rate (HRM), or 75-150 minutes of high-intensity physical activity at 60-85% HRM to maintain and enhance adult fitness. However, commonly cited obstacles to physical activity include time constraints, low motivation, and difficulties in adhering to guidelines. High-Intensity Interval Training (HIIT), requiring less time for exercise, has been shown to deliver equivalent or greater health benefits compared to WHO recommendations. This study aims to assess the impact of HIIT on physical fitness, VO2Max, and social status. Utilizing a literature review method, articles were sourced from Electronic Databases such as PubMed, ScienceDirect, and ProQuest. The results indicate that High-Intensity Interval Training (HIIT) can efficiently enhance physical fitness, significantly impact social status, and do so within a shorter time frame. This makes HIIT an appealing alternative for individuals facing challenges like time constraints, low motivation, or difficulties in adhering to traditional activity guidelines. With improvements observed in physical fitness and VO2Max, HIIT emerges as a compelling option for those seeking a time-efficient yet effective exercise method. Consequently, this research highlights that HIIT not only serves as an efficient strategy for achieving physical fitness and cardiorespiratory health but also contributes to enhancing social aspects. These findings offer valuable insights for designing more acceptable and sustainable physical activity programs within the community.